Body mass index, general fatness, lipid profile and bone mineral density in young women and men - Kopiczko, Anna; Gryko, Karol (Anthropological Review, 2017)
The bone tissue is metabolically active. Throughout the entire life, it undergoes changes in the form of bone resorption processes which are successive, with the participation of the resorbing cells and bone formation processes. The aim of the study was to evaluate mineral density and bone mass tissue and the lipid profile, BMI, total body fat in young females and males. The study involved 100 people (50 females and 50 males) studying in Warsaw at the age of 23,2 ± 4,0 years. The densitometry method of the forearm was used for the assessment of bone mineral density (BMD) and bone mass (BMC). The method of bioelectrical impedance was used for the assessment of body components. Basic body dimensions and indicators were assessed using anthropometric measurements. Body height, body mass and the needs for the densitometry study of the forearm were measured. The total cholesterol concentration was determined in the blood serum using diagnostic kits, as well as high-density lipoprotein (HDL-C) and triglycerides. The concentration of the low-density lipoprotein (LDL-C) was calculated. While in men the occurrence of a significant, positive correlation was stated between the concentration of the HDL cholesterol fraction and the mineral density and T-score index in the ultra-distal point, the analysis of the compounds of mineral density (BMD), bone mass (BMC) of the forearm, T-score index with somatic features in women showed a significant, positive relation between the body weight and the bone mass mineral density and T-score indicator in the proximal point. Also, a significant weak, positive correlation was observed between the BMI, the mineral density and T-score indicator in the proximal point. In men, the occurrence of significant, positive correlations was stated between the body weight and BMC, BMD, T-score indicator in the proximal point of the forearm bone and ultra-distal point. Similar relations were observed between the BMI, mineral density, T-score and bone mass in the proximal point and in the ultra-distal point. Based on several noted weak, positive correlations between the lipid profile and BMD, the results of this study of women and men cannot unequivocally indicate the dependence of the bone tissue state on the lipid level in the blood serum of young women and men. Therefore, the issues raised require further investigation.